Is Alexa female, male, or neutral? A cross-national and cross-gender comparison of perceptions of Alexa's gender and status as a communicator. (December 2022) - Fortunati, Leopoldina; Edwards, Autumn; Edwards, Chad; Manganelli, Anna Maria; de Luca, Federico
Abstract: The gendering of machine agents risks further complicating the social framework in ways that reverberate to humans' relationships and identities. This paper explores how users perceive the gender and status of Amazon's Alexa. We argue that voice-based assistants, particularly those with feminine names and voices, may contribute to reinforcing a retrieval ideology of the feminine as the place of social subordination and contempt. We conducted an online survey of women and men in the US ( n = 322) and Italy ( n = 333). Most (80%) identified Alexa as "female." However, there was a lack of concordance between the gender respondents ascribed to Alexa and their spontaneous use of pronouns in writing. In terms of status, over half of the sample perceived Alexa as an inferior communicator (for Italian respondents, inferiority was associated with perceiving Alexa as female), while over one-third rated Alexa as equal or superior to humans, evidencing the change happening in the ontological order. The few respondents who noticed gender differences in people's interactions with Alexa perceived women to be more courteous, serious and accommodating in their use. Respondent gender and culture comparisons are presented, implications of the findings are discussed, and future research is proposed to reduce harmful impact. Highlights: Most respondents labeled Alexa "female, " showing that the few female cues in design are sufficient for gender attribution. But, only a minority referred to Alexa with feminine pronouns, indicating a lack of consistency in gender attribution. Over 1/3 of the sample considered Alexa a communicator equal or superior to humans, demonstrating fast-changing ontology. Few noticed gender differences in people's use of Alexa, suggesting a lack of awareness of gendered dynamics. VBAs like Alexa may reinforce a retrieval ideology of the feminine as the place of social subordination and contempt.